Barriers to HPV vaccination in marginalized Roma communities in Slovakia - Filakovska Bobakova, Daniela; Plavnicka, Jana; Urbancikova, Ingrid; Edelstein, Michael; Jansen, Danielle; Dankulincova Veselska, Zuzana (Frontiers in Public Health, 2023)
Introduction Limited access to healthcare services leads to lower vaccination rates in marginalized Roma communities (MRCs). This study aimed to explore health system barriers to HPV vaccination faced by people from MRCs from multiple perspectives. Methods The qualitative study was conducted in Slovakia in 2021/22 with 43 community members and health professionals. Data were analyzed using a combination of content analysis and consensual qualitative research. Results A substantial barrier to vaccination is limited coverage of vaccination expenses for certain age categories by health insurance. Moreover, Slovakia faces a significant shortage of healthcare personnel, leading to work overload and a lack of capacity and motivation to address HPV vaccination. Impaired relationships between health care providers and people from MRCs lead to the avoidance of healthcare services, which contributes to insufficient delivery of information and a lack of awareness regarding HPV-related diseases and vaccination. Conclusion Strengthening the capacities of health care providers, expanding the age group covered by health insurance and providing tailored information to people from MRCs are necessary prerequisites to increase the availability of HPV vaccination and enable people to make informed decisions about HPV vaccination.